Effect of soluble fiber in elderly with constipation - Pires, J. F. (2020)
Rationale: Constipation is one of the most common clinical conditions at any age. However, the elderly have a higher risk of development. The evidence suggests that certain care, especially at the food level, may influence the symptomatology of this clinical condition. Methods: The study lasted four weeks, being a simple clinical trial with intervention. Seventy individuals were part of the study and were divided into two groups. Both received nutritional guidance directed to constipation, but only one group received 100% soluble fiber supplement. The individuals were subsequently evaluated in three moments. Results: After four weeks of intervention, gastrointestinal symptomatology improved significantly in both groups, however, there were greater differences in the group where 100% soluble fiber was applied, significantly improving the results of Bristol Scale (p=0.00 vs p=0,001) and in the variable excretion facility (p=0.000 vs p=0.000). Regarding the frequency of defecation also increased in both groups, being statistically different in all moments of evaluation in the group with fiber. Conclusion: Nutritional recommendations that promote adequate fiber intake accompanied by an increase in 100% soluble fiber supplementation seem to have a positive influence on the symptomatology of obstipated individuals.